2020
DOI: 10.3389/fphar.2020.575463
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the Relationship Between the Trough Concentration of Posaconazole and Its Efficacy and Safety in Chinese Patients With Hematological Disorders

Abstract: Posaconazole (PCZ) is effective in preventing and salvage treatment invasive fungal infections in patients with hematologic disorders. However, PCZ displays highly variable individual pharmacokinetics affecting its efficacy and safety. To investigate the correlation between PCZ concentration and efficacy and safety, the following key influencing factors were explored. A total of 285 trough plasma concentrations (C min ) of 81 Chinese patients receiving PCZ oral suspension for prophylaxis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 33 publications
1
16
1
Order By: Relevance
“…Among patients receiving PCZ for the treatment of IFI, PCZ concentrations among patients who failed therapy (0.53 μg mL −1 ) were lower than those who treated successfully (1.06 μg mL −1 ) ( p = 0.024). In our previous study, PCZ C min values of 1.0 μg mL −1 was associated with a >80% probability of successful treatment response ( Jia et al, 2020 ). Similar to a multicenter study of PCZ treatment of IFIs in juvenile (<18 years) with IFIs [the success rate was (5/8) 62.5%] ( Krishna et al, 2007 ), the current study found that 79.2% of patients (19/24) successfully responded to PCZ treatment.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Among patients receiving PCZ for the treatment of IFI, PCZ concentrations among patients who failed therapy (0.53 μg mL −1 ) were lower than those who treated successfully (1.06 μg mL −1 ) ( p = 0.024). In our previous study, PCZ C min values of 1.0 μg mL −1 was associated with a >80% probability of successful treatment response ( Jia et al, 2020 ). Similar to a multicenter study of PCZ treatment of IFIs in juvenile (<18 years) with IFIs [the success rate was (5/8) 62.5%] ( Krishna et al, 2007 ), the current study found that 79.2% of patients (19/24) successfully responded to PCZ treatment.…”
Section: Discussionmentioning
confidence: 95%
“…Dose adjustments were taken according to the current guidelines and the manufacturer’s recommendations ( Vicenzi et al, 2018 ). PCZ trough plasma concentrations were determined using a previously described ultra-high-performance liquid chromatograph-tandem mass spectrometry method (UPLC-MS/MS, Waters, United States) ( Jia et al, 2020 ). The analytical range was 0.025–5.00 μg mL −1 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The guidelines recommend PCZ as primary prophylaxis drug in high-risk immunocompromised patients, but in our study, all 31 patients had received voriconazole for antifungal prophylaxis before the onset of mucormycosis. There is only PCZ oral suspension in our hospital, and the PCZ plasma concentration is usually insufficient, which may be lead to poor clinical effectiveness ( Jia et al, 2020 ). Therefore, the doctors in our hospital often choose voriconazole to prevent fungal infections.…”
Section: Discussionmentioning
confidence: 99%
“…PCZ plasma concentration in some patients was monitored, but 50% of that did not reach 1.0 mmol/L. Previous studies have shown that insufficient PCZ plasma concentration indicated a high failure rate of prophylaxis and therapy of invasive fungal disease ( Chae et al, 2015 ; Jia et al, 2020 ). Insufficient PCZ plasma concentration may also be an important factor in the high mortality of patients in our study; however, in our study, only some patients had measured PCZ plasma concentration, so it has not been used to establish the death prediction model.…”
Section: Discussionmentioning
confidence: 99%